The crustin-like peptide plays opposite role in shrimp immune response to Vibrio alginolyticus and white spot syndrome virus (WSSV) infection. Issue 66 (July 2017) - Sun, Baozhen; Wang, Zhi; Zhu, Fei
Abstract: Crustin is an antimicrobial peptide (AMP) that plays a key role in innate immunity of crustaceans. In this study, we cloned the entire 660 bp crustin-like sequence with a 507 bp open reading frame encoding a 168 amino acid from Marsupenaeus japonicus . The crustin-like gene was primarily expressed in gills and over-expressed in shrimp hemocytes after challenge with WSSV or Vibrio alginolyticus . After knockdown crustin-like gene using specific double-stranded RNA (CRU-dsRNA), IMD, Rab7, L-lectin, mitogen-activated protein kinase, p53, prophenoloxidase and Rho were down-regulated and nitric oxide synthase, myosin and tumor necrosis factor-α were up-regulated in hemocytes at 24 h post dsRNA treatment. After WSSV challenge, The mortality, WSSV copy number and expressions of WSSV immediate early genes (IE1, IE2, DNA polymerase, VP28) were both decreased but the apoptosis rate was increased in CRU-dsRNA-treated shrimps, indicating that WSSV may take advantage of crustin-like to benefit its replication. After silenced the crustin-like, the results of phagocytosis showed that the phagocytic rate of shrimp hemocytes on WSSV decreased significantly. In contrast, the absence of crustin-like in shrimps increased the mortality following V. alginolyticus challenge, indicating that crustin-like may play a positive role in the antibacterial process. The phagocytosis experiment showed there was a higher phagocytosis rate of hemocytes after CRU-dsRNA treatment. The result indicated that V. alginolyticus may be able to use crustin-like to avoid phagocytosis of shrimp hemocytes. These results further added to our understanding of the function of crustin-like peptide and also provided its potential role in innate immunity in shrimp. Highlights: The entire 660 bp crustin-like sequence was cloned from Marsupenaeus japonicus. The crustin-like may play a positive role in the antibacterial process. WSSV may take advantage of crustin-like to benefit its replication.